Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3847/1538-4357/ac9eaf
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Beam Variations on Power Spectrum Estimation for 21 cm Cosmology. I. Simulations of Foreground Contamination for HERA

Abstract: Detecting cosmological signals from the Epoch of Reionization (EoR) requires high-precision calibration to isolate the cosmological signals from foreground emission. In radio interferometry, the perturbed primary beams of antenna elements can disrupt the precise calibration, which results in the contamination of the foreground-free region, or the EoR window, in the cylindrically averaged power spectrum. For the Hydrogen Epoch of Reionization Array (HERA), we simulate and characterize the perturbed primary beam… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 77 publications
0
1
0
Order By: Relevance
“…This was subsequently confirmed experimentally by varying feed height and observing changes in autocorrelations. Kim et al (2022) found in simulation that feed positioning should be accurate to the 1 centimeter level in position and 1°in tilt to minimize foreground leakage in power spectra. This leakage is caused by calibration errors, as the feed positioning offset impacts array redundancy.…”
Section: Phase II Feedmentioning
confidence: 98%
“…This was subsequently confirmed experimentally by varying feed height and observing changes in autocorrelations. Kim et al (2022) found in simulation that feed positioning should be accurate to the 1 centimeter level in position and 1°in tilt to minimize foreground leakage in power spectra. This leakage is caused by calibration errors, as the feed positioning offset impacts array redundancy.…”
Section: Phase II Feedmentioning
confidence: 98%
“…noiseless simulations. We will investigate the effects of realistic noise, radio-frequency interference, realistic errors in beam models, calibration accuracy, realistic antenna position, and beam variations (Orosz et al 2019;Aguirre et al 2022;Kim et al 2022Kim et al , 2023.…”
Section: Future Workmentioning
confidence: 99%
“…In general, precisely measuring or modeling the complex beam patterns antenna elements over the entire bandwidth of operation is difficult and errors can manifest due to various factors: environmental conditions such as soil moisture and electrical properties variation, manufacturing defects, and positioning errors, mutual coupling and cross-talk between individual antennas in the interferometer [6,7]. In addition, all of these effects can vary with time.…”
Section: Causes Of Beam Errorsmentioning
confidence: 99%